2008
DOI: 10.1038/npre.2008.2355
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Selective Auditory Attention in Rats (Dissertation)

Abstract: of the Dissertation Neural Mechanisms of Selective Auditory Attention in Rats by Lung-Hao Tai Doctor of Philosophy in Neuroscience Stony Brook University 2008How does attention modulate sensory representations? In order to probe the underlying neural mechanisms, we established a simple rodent model of modality-specific attention. Rats were trained to perform distinct auditory two-tone discrimination and olfactory odor discrimination in a two alternative choice (2AC) paradigm.To determine auditory cortex's role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…3), in which target stimuli were similarly sub-optimal, no widespread suppression was observed when the auditory stimulus was selectively attended. Intermodal attention enhanced responses in some auditory cortical neurons and suppressed it in others 2220 , but it did not generate the large population effects observed in task-engaged suppression. Second, suppression resulting from engagement was general, for both target and non-target stimulus, and appeared independent of neural selectivity; responses selective for the location of the sound were not preferentially enhanced during the sound localization task (Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…3), in which target stimuli were similarly sub-optimal, no widespread suppression was observed when the auditory stimulus was selectively attended. Intermodal attention enhanced responses in some auditory cortical neurons and suppressed it in others 2220 , but it did not generate the large population effects observed in task-engaged suppression. Second, suppression resulting from engagement was general, for both target and non-target stimulus, and appeared independent of neural selectivity; responses selective for the location of the sound were not preferentially enhanced during the sound localization task (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, there was a slight, albeit nonsignificant, trend toward enhancement in the auditory block, as expected from recordings in an auditory area during an auditory task. A subset of single neurons showed strong modulation (either positive or negative) between the auditory and olfactory blocks, so that the very small net change between the blocks reflected a balance between the changes in the two conditions ( not shown; see 22 ). These results are inconsistent with the hypothesis that engaging in an auditory task per se suppresses responses in auditory cortex, and support the interpretation advanced above that suppression results from engaging in a task, regardless of sensory modality.…”
Section: Resultsmentioning
confidence: 99%
“…3a). Using a similar behavioral paradigm, we have previously shown that muscimol inactivation of the auditory cortex impairs auditory performance on a simple auditory discrimination task but has no effect on an olfactory discrimination task 11 .…”
Section: Resultsmentioning
confidence: 98%